THE SKILL OF USING PHRASEOLOGY IN BAYRAM ALI'S STORY "TUNKEZAR CHILDREN" - Aziza Dilmurod qizi Uralova (International Engineering Journal For Research & Development, 2022)
In this article, Bayram Ali's skill in using phraseology in the story "Tunkezar children" is explained with examples.